Understanding the mechanism of texturization, and the relationship between properties of wheat gluten and texturized vegetable protein - Roberts, Ryan (Kansas State University, 2013)
Texturized vegetable protein (TVP) based foods offer several advantages compared to animal protein, including lower costs and improved health benefits. Wheat gluten is often processed using extrusion to produce TVP. Processing aids, such as reducing agents (example, cysteine and sodium metabisulfite) and pH modifiers (example, tetra potassium phosphate) aid in texturization. Reduction of sulfhydryl groups, cleavage of disulfide bonds, and reformation of bonds between elongated protein molecules results in protein aggregation and texturization. This study focused on development of a fundamental understanding of these mechanisms for texturization using analytical tools such as the phase transition analyzer (PTA), in combination with lab- and pilot-scale extrusion. The abovementioned three chemicals were added to four varieties of gluten. The control treatment had no additives. PTA was used to understand the operative flow properties of gluten in an environment similar to an extrusion system. Addition of sulfite (0.18%) and cysteine (0.18%) lowered the thermal softening (Ts:36.6-44.1 °C) and thermal flow (Tf:79.6-105.6 °C) temperatures of all varieties of gluten as compared to the controls (Ts:38.8-48.2 °C; Tf:91.7-112.2 °C). Phosphate (3%) did not have the same lowering effect on Ts (40.2-47.0 °C) and Tf (96.2-108.2 °C), indicating a different mechanism. Extrusion studies were conducted to gain an understanding of the reformation of disulfide bonds and texturization. Two of the varieties of gluten, a “superior” one that texturizes well and an “inferior” gluten requiring texturizing aids, were processed on a lab-scale extruder. Pilot scale extrusion was used to process the other two glutens (“superior” varieties) to obtain commercial quality products, which were evaluated for degree of texturization (hydration rate, absorption index and integrity). During lab-scale extrusion, texturization was observed only in the case of phosphate and corresponded with an increase in specific mechanical energy (SME) as compared to the control, indicating disulfide bond reformation. Phosphate also led to significantly (p<0.05) better texturization during pilot-scale extrusion, although SME trends were different due to higher in-barrel moisture and a more ideal extrusion system. Fourier Transform Infrared Spectroscopy was used to examine protein structural changes and indicated a loss of α-helix structure in TVP with an increase in β-sheet formation.
Keywords: Wheat gluten; Extrusion; Texturization; Sulfite; Cysteine; Phosphate; Agriculture, General (0473); Biochemistry (0487); Chemistry, Agricultural (0749); Engineering, Agricultural (0539); Food Science (0359)